(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
A capillary barrier system is a promising alternative measure for controlling rainfall infiltration into unsaturated residual soil slopes. Although, system with capillary barrier effect has been successfully applied to avert rainfall infiltration in dry and semi-dry climates, its application in humid climates with high precipitation rate is still unsatisfactory. Therefore, this paper evaluates the performance of a modified capillary barrier system with transport layer under humid climatic conditions. The capillary barrier system and the transport layer were simulated with Grade V and Grade VI soils and gravel, respectively. The system was subjected to various rainfall intensities using saturated/unsaturated seepage analysis. When the initial suction of 32 kPa was assigned to the system and subjected to the worst rainfall condition for 24-hour duration, the breakthrough time increases with increase in the thickness of grade VI residual soil layer in the conventional capillary barrier system and the maximum diversion length achieved is less than 2 m. However, when a transport layer was placed at the interface of the grade V and grade VI soils, the diversion length increases to 15 m and avert breakthrough occurrence under the same condition. Therefore, the inclusion of transport layer in a residual soil capillary barrier system improved its performance and prevent breakthrough occurrence.